2015
DOI: 10.1021/acs.jpclett.5b00934
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Properties in Silver Clusters

Abstract: The properties of Ag nanoclusters are not as well understood as those of their more precious Au cousins. However, a recent surge in the exploration of strategies to tune the physicochemical characteristics of Ag clusters addresses this imbalance, leading to new insights into their optical, luminescence, crystal habit, metal-core, ligand-shell, and environmental properties. In this Perspective, we provide an overview of the latest strategies along with a brief introduction of the theoretical framework necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 89 publications
0
150
0
Order By: Relevance
“…Synthesis of Au 2 Cu 6 (PPh 2 Py) 2 (AdmSH) 6 nanoclusters:C uCl (0.0198 g, 0.2 mmol) was dissolved in CH 3 CN (5 mL) and CH 3 OH (1) and UV light (2). Au gold, Cl blue, Cu green, Pviolet, Syellow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of Au 2 Cu 6 (PPh 2 Py) 2 (AdmSH) 6 nanoclusters:C uCl (0.0198 g, 0.2 mmol) was dissolved in CH 3 CN (5 mL) and CH 3 OH (1) and UV light (2). Au gold, Cl blue, Cu green, Pviolet, Syellow.…”
Section: Methodsmentioning
confidence: 99%
“…Atomically precise noble-metal nanoclusters (NCs) have attracted extensive research interest, [1][2][3][4][5][6][7] and various NCs (such as gold, silver,a nd bimetallic NCs) have been successfully synthesized in the past decades. [1,[8][9][10][11][12] It is generally accepted that the structure of these NCs determines their physical and chemical properties (e.g., the electrochemical, [13] catalytic, [1b, 5, 14] and optical properties), [9a,15] and is fundamentally important for the related mechanistic studies.…”
mentioning
confidence: 99%
“…Aikens showed that the icosahedral core may be viewed as a Ag 13 +5 core surrounded by six Ag 2 S 3¯ motifs leading to an eight electron formal charge on the entire Ag 25 cluster. This type of electronic distribution can also be understood by calculating the number of free electrons (n e ) present in [Ag 25 (SR) 18 ]¯ via the relationship n e = Nυ-M-z, 33,34 where N is the number of Ag atoms, υ is the valence (1 for Ag), M is the number of mono-thiol ligands, and z is the overall cluster charge. Thus, the number of free electrons in [Ag 25 (SPhMe 2 ) 18 ]¯, can be found by n e = 25×1-18-(-1) = 8, corresponding to the stable superatom electronic configuration 1S 2 |1P 6 |, where S and P represent the angular momentum quantum numbers of the superatomic orbitals, and vertical lines represent shell-closure with a large gap between highest occupied molecular orbitals (HOMO) and lowest unoccupied molecular orbitals (LUMO).…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Furthermore,t he aggregation is affected by the restriction of intramolecular rotation (RIR), and the high rigidity of the outer ligands enhances the fluorescence of the Au 2 Cu 6 nanoclusters. This study thus presents an ovel strategy for enhancing the luminescence of metal nanoclusters (by the aggregation of active metal complexes with inert metal atoms), and also provides fundamental insights into the controllable synthesis of highly luminescent metal nanoclusters.Atomically precise noble-metal nanoclusters (NCs) have attracted extensive research interest, [1][2][3][4][5][6][7] and various NCs (such as gold, silver,a nd bimetallic NCs) have been successfully synthesized in the past decades. [1,[8][9][10][11][12] It is generally accepted that the structure of these NCs determines their physical and chemical properties (e.g., the electrochemical, [13] catalytic, [1b, 5, 14] and optical properties), [9a,15] and is fundamentally important for the related mechanistic studies.…”
mentioning
confidence: 99%